Computer-based multiple component cognitive training in children with ADHD: a pilot study - Yingying Wu; Lingzi Xu; Zhaomin Wu; Xiaolan Cao; Gui Xue; Yufeng Wang; Binrang Yang (BMC, 2023)
Abstract Background ADHD is associated with deficits in executive functions. Cognitive training is a promising nonpharmacological intervention for ADHD, however, there is insufficient evidence to guide the selection of training for individuals with ADHD. This pilot study aims to investigate the efficacy of executive function training targeting key executive dysfunctions in ADHD, compared with general executive function training which targets other executive functions. Methods A total of 127 subjects (6-12 years) diagnosed with ADHD were allocated to receive one of two different cognitive trainings. ADHD symptoms and cognitive functions were evaluated using parent-rated scales and CANTAB cognitive assessments. All participants were required to complete 48 training sessions within a two-month period. Results 94 out of 127 children completed the required training and assessments. Both ADHD executive function training group and general executive function training group showed significant improvement in ADHD symptoms on the ADHD Rating Scale and in executive function on the assessment of CANTAB. There was no significant difference in improvements between the two groups. Subgroup analysis suggested that children who had ADHD-RS total scores less than or equal to 28 at baseline showed greater improvement following ADHD executive function training. Conclusions This study indicates that cognitive training can improve ADHD symptoms and executive function, with no difference in efficacy between targeted and generalized cognitive training. In addition, individuals with lower symptom severity may benefit more from training targeting key ADHD executive dysfunctions.